Digital Governance and its Relationship to Enhancing Financial Inclusion in Libyan Commercial Banks (A Field Study from the Perspective of a Sample of Customers at North Africa Bank- Al-Bayda) - Nisreen Saad Imraga (Journal of Scientific and Human Dimensions, 2026)
This study aimed to investigate the relationship between digital governance and financial inclusion in Libyan commercial banks using a descriptive-analytical approach, based on 198 valid questionnaires collected from a sample of customers. The findings revealed that the majority of respondents were male (77.3%), aged 30–40 (57.5%), and university graduates (55.1%), while indicating that both digital governance and financial inclusion levels were perceived as "moderate." Furthermore, the results demonstrated a statistically significant correlation between the dimensions of digital governance (participation, transparency, accountability, and digital auditing) and financial inclusion; consequently, the study recommended launching unified digital platforms to provide real-time access to legislation and services, thereby enhancing institutional trust and ensuring effective, sustainable financial inclusion.
Keywords: Digital Governance; Financial Inclusion; North Africa Bank; Al-Bayda; Libya